Intestinal Colonization Dynamics of Vibrio cholerae - Almagro-Moreno, Salvador (Public Library of Science, 2015)

(untitled) (PLoS Pathog)
To cause the diarrheal disease cholera, Vibrio cholerae must effectively colonize the small intestine. In order to do so, the bacterium needs to successfully travel through the stomach and withstand the presence of agents such as bile and antimicrobial peptides in the intestinal lumen and mucus. The bacterial cells penetrate the viscous mucus layer covering the epithelium and attach and proliferate on its surface. In this review, we discuss recent developments and known aspects of the early stages of V. cholerae intestinal colonization and highlight areas that remain to be fully understood. We propose mechanisms and postulate a model that covers some of the steps that are required in order for the bacterium to efficiently colonize the human host. A deeper understanding of the colonization dynamics of V. cholerae and other intestinal pathogens will provide us with a variety of novel targets and strategies to avoid the diseases caused by these organisms.